ANALYSIS OF SERVICE QUALITY BASED ON PATIENT’S ASSESSMENT AND EXPECTATION IN MOTHER AND CHILD HOSPITAL OF SURABAYA - Andini Yulina Pramono (Universitas Airlangga, 2019)
Background: Service quality at Kendangsari Merr Mother and Child Hospital is expected to compete with other private hospitals, especially maternity hospitals. Nevertheless, several months after its opening, the hospital received a few complaints from its patients.Aims: This study analyzed patient satisfaction to increase the service quality at Kendangsari Merr Mother and Child Hospital using RATER parameters.Methods: This study was an observational study that used a cross-sectional design. It was conducted at Kendangsari Merr Mother and Child Hospital from 27 to 31 October 2014. The respondents were taken from a total population of all inpatients and outpatients during the survey. The instrument used was a questionnaire using service quality indicators, such as Reliability, Assurance, Tangible, Empathy and Responsiveness (RATER) parameters.Results: The respondents’ assessment of the service quality at Kendangsari Merr Mother and Child Hospital was good with an average score of 81%. In terms of assurance, tangible, and empathy factors, most of the patients assessed that they received better services than what they expected.Conclusion: Some other poor aspects of the service quality should be improved. They include the punctuality of doctor practice, doctors’ skills, public facilities, politeness and awareness of staff pharmacists in treating patients’ drugs as prescribed. Keywords: assessment, expectation, patient satisfaction, service quality.